MYTHOLOGISING THE TOPOS OF THE BANQUET IN “CASTLE RACKRENT” BY MARIA EDGEWORTH AND “PAN CHALAWSKI” BY GRIGORYI KVITKA-OSNOWYANENKO - Czyk, Denis (Porównania, 2015)
The article offers a comparative analysis of the topos of banquet in the novel by the Ukrainian writer Kvitka-Osnovyanenko Pan Chalawski (1839) and the Irish writer Maria Edgeworth Castle Reckrent (1800). Both novels present the social system and the degree of the nobility’s awareness in the 19th century whose lifestyle based on parties, fun and other carnivalesque rituals, is fading away. The works present a confrontation of good old times with the contemporary, decadent and de-void of former grandeur form of degraded ritual. The degraded ritual still illustrates the former social structure and inter-class relations though in a mocking and critical way. The topos of the banquet and fun unveils the difficult Ukrainian and Irish socio-political reality.